Improving Critical Thinking Character Through Numeracy Literacy For Elementary School Students - Anggraini, Dian Mustika; Mubarok, Husni; Sari, Ima Frafika (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
Numeracy literacy is very important for elementary school students because it provides a basis for applying mathematics in everyday life. Numeracy literacy requires students to think critically in solving problems. Moreover, elementary school is early childhood education to start getting used to thinking through research and analysis. Researchers use qualitative research in literature studies by reviewing various sources such as books, articles, modules, and final research assignments. The results of the research are that there are several ways to shape the critical thinking character of elementary school students with numeracy literacy, namely 1) using interactive learning models such as project-based learning and problem-based learning; 2) application of numeracy literacy in various classroom activities; and 3) conveying meaningful mathematical values during learning. A teacher can use these three methods optimally, provided that a teacher must also apply numeracy literacy in everyday life. So it will be easier for students to imitate and apply it.